Memory Effect: How the Initial Structure of Nanoparticles Affects the Performance of De-Alloyed PtCu Electrocatalysts? - Angelina S. Pavlets; Anastasia A. Alekseenko; Ilya V. Pankov; Sergey V. Belenov; Vladimir E. Guterman (Energies, 2022)
An important feature of this research is the investigation of the de-alloyed catalysts based on the nanoparticles with a simple structure (alloy) and a complex structure (gradient). The resulting samples exhibit the 2–4 times higher mass activity in the ORR compared with the commercial Pt/C. The novelty of this study is due to the application of the express-electrochemical experiment to register the trend of changes in the ORR activity caused by rearranging the structure of bimetallic nanoparticles. The state-of-the-art protocol makes it possible to establish the dependence of properties of the de-alloyed catalysts on the nanoparticles’ structure obtained at the stage of the material’s synthesis. The study shows the possibility of determining the rate of the ongoing reorganization of bimetallic nanoparticles with different architectures. The PtCu/C electrocatalysts for proton-exchange membrane fuel cells presented in this work are commercially promising in terms of both the high functional characteristics and the production by facile one-pot methods.